Apolipoprotein A5 fifteen years anniversary: Lessons from genetic epidemiology - Hubacek, Jaroslav A (Gene, 2016)
Apolipoprotein A5 (APOA5) is a small protein, expressed predominantly in the liver. In plasma, it is located on triglyceride rich lipoprotein particles (chylomicrones and VLDL) and on HDL. Plasma concentration of apolipoprotein A5 is very low, suggesting rather regulatory (activation of lipoprotein lipase, …) than structural function. APOA5 is an important determinant of plasma triglyceride concentration; this effect has been confirmed both on animal models, as well as on human studies. Minor alleles of three commonly analysed variants within this gene (rs662799, rs3135506, rs2075291) are associated with higher plasma TG values and increased risk of myocardial infarction, with some important interethnic differences observed. Further roles of APOA5; determination of BMI, diabetes and last but not least nutri- and pharmaco-genetic interactions are suggested, but without the definitive conclusions.
Keywords: apolipoprotein A-V; kardiovaskulární nemoci; Cardiovascular Diseases; Apolipoprotein A-V; Polymorphism, Single Nucleotide; lidé; jednonukleotidový polymorfismus; Humans; triglyceridy; Triglycerides